Barriers to the provision of community-based mental health services at primary healthcare level in northern Nigeria - A mixed methods study - Emmanuel Ejembi Anyebe; V.O. Olisah; S.N. Garba; H.H. Murtala; A. Danjuma (Elsevier, 2021)
This study examined the barriers associated with the level of community-based mental health services in three selected States in northern Nigeria. Both quantitative and qualitative data were collected from a convenient sample of 191 primary healthcare (PHC) service providers and a purposive sample of 13 primary healthcare system administrators and managers at both State and Local government levels through a WHO/WFMH 10-factor questionnaire and literature-derived guide for in-depth interviews (IDIs). Quantitative data analysis was undertaken using simple descriptive measures (with the use of IBM Statistical Product and Service Solutions (SPSS) 23.0) while the qualitative data was thematically analysed to complement the quantitative data. Results show that in all the study States, poor funding, lack of skilled mental health human resource and inadequate training of available personnel were identified as the major barriers to provision of mental health services at the community level. Socio-cultural factors such as community rejection of the services, stigma and misconceptions were reported as second-grade barriers. It is concluded that PHC administrators, coordinators and service providers agree that fallouts of policy failure and lack of political will at Federal, State and Local government levels and socio-cultural dynamics constitute barriers to community based mental health services. Efforts towards improving the provision of these services need to focus more on healthcare policy issues and political machinery of the governments while motivating available service providers to increase community psycho-education in their respective centres and host communities. This should be done as short-, medium- and long-term measures.